2022
DOI: 10.3390/plants11101376
|View full text |Cite
|
Sign up to set email alerts
|

Bioremoval of Yttrium (III), Cerium (III), Europium (III), and Terbium (III) from Single and Quaternary Aqueous Solutions Using the Extremophile Galdieria sulphuraria (Galdieriaceae, Rhodophyta)

Abstract: The lanthanides are among the rare earth elements (REEs), which are indispensable constituents of modern technologies and are often challenging to acquire from natural resources. The demand for REEs is so high that there is a clear need to develop efficient and environmentally-friendly recycling methods. In the present study, living cells of the extremophile Galdieria sulphuraria were used to remove four REEs, Yttrium, Cerium, Europium, and Terbium, from single- and quaternary-metal aqueous solutions. Two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Terbium was the element most easily adsorbed by the G. sulphuraria ACUF427. These findings agree with the results shown in the previous work [22], according to which the same Galdieria strain in the same quaternary system preferred terbium (in the same way as europium) and the highest removal rate was obtained at pH 4.5. A comparison between bioaccumulation [22] and biosorption of the same algal strain with the same metal system, carried out in the present study, showed comparable performance between metabolically active and inactive algae, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Terbium was the element most easily adsorbed by the G. sulphuraria ACUF427. These findings agree with the results shown in the previous work [22], according to which the same Galdieria strain in the same quaternary system preferred terbium (in the same way as europium) and the highest removal rate was obtained at pH 4.5. A comparison between bioaccumulation [22] and biosorption of the same algal strain with the same metal system, carried out in the present study, showed comparable performance between metabolically active and inactive algae, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Bioaccumulation is an active metabolic process which includes the interaction of metals with the cell surface (passive adsorption), followed by an active metabolism-dependent adsorption involving the transport of metal ions across the cell membrane into the cytoplasm, which is much slower than biosorption. A recent study on living cells of G. sulphuraria highlighted, particularly, that the adsorption of yttrium, cerium, europium, and terbium is pH-dependent [22].…”
Section: Introductionmentioning
confidence: 99%
“…In a study completed by Iovinella et al [ 68 ], the removal of four rare earth elements (REEs): yttrium (Y), cerium (Ce), europium (Eu), and terbium (Tb) was achieved using two strains of Galdieria sulphuraria. SAG 107.79 and ACUF 427 were two strains subjected to metal solutions at pH levels ranging from 2.5 to 5.5.…”
Section: Cyanidiales and Their Effectiveness In Heavy Metal Removalmentioning
confidence: 99%
“…The effect of pH was studied by Iovinella et al [ 68 ], for the removal of REEs: Y, Ce, Eu, and Te using two strains of Galdieria sulphuraria: SAG 107.79 and ACUF 427. The range of pH levels was 2.5 to 5.5.…”
Section: Cyanidiales and Their Effectiveness In Heavy Metal Removalmentioning
confidence: 99%
“…In addition to using light as a fuel source, G. sulphuraria utilises a variety of complex carbon sources for growth [11]. Consequently, G. sulphuraria is of great interest for use in biotechnology for the degradation of lignocellulosic materials [12], as well as the remediation of rare earth metals [13] [14] and wastewater treatments [15].…”
Section: An Example Of Known Photosynthetic Extremophiles Belong To Thementioning
confidence: 99%